Initial experience with external thoracic stabilization by the »figure of eight« osteosynthesis in polytraumatized patients with flail chest injury - Ivančić, Aldo, liječnik (Array, 2009)
Abstract: The aim of this study was to describe initial experience with external thoracic stabilization by the »figure of eight« osteosynthesis in polytraumatized patients with flail chest injury. From January 2002, fifteen patients underwent this surgical procedure at the University Hospital of Rijeka. Their mean age was 52 ± 13.69 (range 18–65) and mean ISS was 29.8 (range: 20–41). Twelve patients were weaned from artificial respiration on same day when operated, two on the post-operative day 1, and one on the post-operative day 2. Their stay within the intensive care unit following extubation was within the range of 1–12 days (mean 3.93 ± 2.99). The early external thoracic stabilization by the »figure of eight« osteosynthesis was followed by swift extubation of patient and direct normalization of respiratory parameters. This method contributed significantly to patient’s shorter stay within the intensive care unit.